A history of risk science : concepts and principles of risk analysis - Aven, Terje (Routledge advances in management and business studies, 2026)
Risk has been handled as long as there have been humans on Earth. However, the risk field is a young discipline; systematic attempts to access and handle risk - explicitly conceptualizing and expressing risk - in society are a recent endeavour. This book presents a history of risk science and risk analysis highlighting concepts and principles for understanding, assessing, communicating, managing and governing risk.The author presents and discusses key contributions to risk science using a historical lens and from the perspective of a risk scientist. The book strengthens our understanding of what risk science is and how it has evolved by exploring fundamental topics such as risk characterization, risk perception, risk communication, risk handling and decision-making and concludes with reflection on the future of risk science, and in particular what we can learn from its history.A History of Risk Science will be essential reading for risk researchers and graduate students as well as scholars from associated fields applying risk-related analysis to their work.